ANALISIS PEMBERDAYAAN DAN PENILAIAN KINERJA PEGAWAI KELURAHAN SUKARAME BARU DALAM MENINGKATKAN PELAYANAN MASYARAKAT PADA MASA PANDEMI COVID 19 - Sukismanto Aji; Tina MB Virgawendra (Universitas Bandar Lampung (UBL), 2023)
The purpose of this study is to analyse the empowerment and performance assessment of Sukarame Baru urban village employees in improving community services during the covid-19 pandemic. This research was conducted directly in the Sukarame Baru urban village using observation and interview methods. Based on the results of the research conducted, there are conclusions that: (1) To carry out online community services during the covid 19 pandemic, it is necessary to be supported by adequate human resources, facilities and infrastructure and office facilities. (2) There are employees who are always ready to provide services to the community. (3) There are still delays in completing work (4) There are still employees who lack discipline when entering and leaving the office.